ANALYSIS OF PRODUCTION SCALE (RETURN TO SCALE) OF RICE FARMING IN SUNGGAL DISTRICT, DELI SERDANG REGENCY, NORTH SUMATRA - Riris Nadia Syafrilia Gurning; Sakral Hasby Puarada (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study was conducted in Sunggal District, Deli Serdang Regency, North Sumatra, with the objective of analyzing the production scale of rice farming through the Return to Scale (RTS) approach. The research used primary data collected from 100 rice farmers selected using simple random sampling. Production factors analyzed included land area, fertilizer, and labor. The analytical method employed was a Cobb–Douglas production function estimated using multiple linear regression in logarithmic form. The RTS value was obtained by summing the elasticity coefficients of the production factors. The results showed that the sum of production elasticities was 1.241, indicating that rice farming in Sunggal District operates under increasing returns to scale. This condition implies that proportional increases in production inputs result in a more than proportional increase in output. Therefore, rice production in the study area still has the potential to be increased through the expansion and optimization of production inputs